Advances in Wheat Genetics: From Genome to Field 2015
DOI: 10.1007/978-4-431-55675-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the Genetic Diversity for Grain Quality in Bread Wheat Through Alien Introgression

Abstract: Diverse technological purposes of bread wheat grain requires a broadening the genetic base of selection for quality traits. Introgressions potentially may affect technological properties of grain and fl our and add to a genetic variability of the trait. The aim of this work was to investigate the infl uence of introgressions from exotic tetraploid wheat Triticum timopheevii and wild cereal species, Aegilops speltoides and Aegilops markgrafi i into bread wheat on grain quality. The introgression from T. timophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Вместе с ним и другие гены близкородственных видов можно использовать для увеличения содержания белка в зерне мягкой пшеницы (De Pace et al, 2001;Zanetti et al, 2001;Kunert et al, 2007) и для улучшения хлебопекарных свойств (Garg et al, 2014). Источниками высокого содержания клейковины в зерне могут быть виды T. timophee vii, Aegilops speltoides (Pshenichnikova et al, 2015), а также Ae. markgrafii.…”
Section: Grain Hardness Pina-d1/5ds Pinb-d1/5dsunclassified
“…Вместе с ним и другие гены близкородственных видов можно использовать для увеличения содержания белка в зерне мягкой пшеницы (De Pace et al, 2001;Zanetti et al, 2001;Kunert et al, 2007) и для улучшения хлебопекарных свойств (Garg et al, 2014). Источниками высокого содержания клейковины в зерне могут быть виды T. timophee vii, Aegilops speltoides (Pshenichnikova et al, 2015), а также Ae. markgrafii.…”
Section: Grain Hardness Pina-d1/5ds Pinb-d1/5dsunclassified
“…This parameter well correlates with wet gluten content (Kozmina 1969;Kulkarni et al 1987;Zhang et al 2008). Recently, it has been shown that the introgression from Triticum timopheevii in the same region of the short arm of 2A chromosome significantly improves this trait (Pshenichnikova et al 2015). The introgressed segment from Ae.…”
Section: Discussionmentioning
confidence: 97%